NURSE PERFORMANCE IN PROVIDING CARE FOR PATIENTS WITH MENTAL DISORDERS AT THE MENTAL HOSPITAL OF SOUTHEAST SULAWESI PROVINCE: MENTAL DISORDERS - Armayani, Armayani; Said, Faridah Mohd; Nambiar, Nisha; Pratiwi, Dewi Sari (STIKes Mandala Waluya Kendari, 2025)
Performance reflects the level of success in carrying out organizational activities. Higher nurse performance facilitates the achievement of organizational goals, while poor performance hinders progress and disrupts planned activities. This study aims to identify factors influencing nurse performance in caring for patients with mental disorders at the Southeast Sulawesi Provincial Mental Hospital. Methods: This study used a quantitative, correlational analytic design with a cross-sectional approach. The population consisted of 56 nurses, with a sample of 36 respondents selected using total sampling based on the Slovin formula. Data were analyzed using the Chi-Square test. Results: The study found significant relationships between several factors and nurse performance in caring for patients with mental disorders. Work attitude (ρ = 0.001 < α = 0.05), workload (χ² = 13.107 ≥ χ²ₜₐᵦₗₑ = 5.591; ρ = 0.001 < α = 0.05), compensation (ρ = 0.000 < α = 0.05), and skills (ρ = 0.000 < α = 0.05) were all significantly associated with nurse performance. Conclusion: Work attitude, workload, compensation, and skills are significantly related to nurse performance in caring for patients with mental disorders at the Southeast Sulawesi Provincial Mental Hospital. Future research is recommended to explore additional factors, such as work motivation and work environment, that may influence nurse performance.